2022
DOI: 10.1126/sciadv.add6391
|View full text |Cite
|
Sign up to set email alerts
|

Expression of expanded GGC repeats within NOTCH2NLC causes behavioral deficits and neurodegeneration in a mouse model of neuronal intranuclear inclusion disease

Abstract: GGC repeat expansions within NOTCH2NLC have been identified as the genetic cause of neuronal intranuclear inclusion disease (NIID). To understand the molecular pathogenesis of NIID, here, we established both a transgenic mouse model and a human neural progenitor cells (hNPCs) model. Expression of the NOTCH2NLC with expanded GGC repeats produced widespread intranuclear and perinuclear polyglycine (polyG), polyalanine (polyA), and polyarginine (polyR) inclusions, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…In addition, eight PD patients and one healthy control were identified with intermediate-length NOTCH2NLC GGC repeat expansions (41-60 repeats), but the association between the intermediate-length NOTCH2NLC GGC repeat expansions and PD is not well established in our study. It had been reported that intermediate-length GGC repeat expansions in NOTCH2NLC may be associated with PD in two different studies, but such intermediate repeat Furthermore, widespread of NOTCH2NLC-polyG inclusions may cause neuronal death from proteotoxic stress, abnormalities in mitochondrial dysfunction, ubiquitin-proteasomal and autophagosomal-lysosomal systems, and neuroinflammation [17,[22][23][24][25]29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, eight PD patients and one healthy control were identified with intermediate-length NOTCH2NLC GGC repeat expansions (41-60 repeats), but the association between the intermediate-length NOTCH2NLC GGC repeat expansions and PD is not well established in our study. It had been reported that intermediate-length GGC repeat expansions in NOTCH2NLC may be associated with PD in two different studies, but such intermediate repeat Furthermore, widespread of NOTCH2NLC-polyG inclusions may cause neuronal death from proteotoxic stress, abnormalities in mitochondrial dysfunction, ubiquitin-proteasomal and autophagosomal-lysosomal systems, and neuroinflammation [17,[22][23][24][25]29].…”
Section: Discussionmentioning
confidence: 99%
“…Dementia-dominant and essential tremor-dominant phenotypes usually have a purer GGC repeat. There are also other possible mechanisms, including the toxicity of polyG-containing protein, the toxicity of repeat RNA, and the methylation status of NOTCH2NLC [17,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these new CGG repeatopathies reside within the 5’ UTRs, like the CGG repeat in FMR1 , and there is already evidence of convergent disease mechanisms triggered by these new repeats with those already established in Fragile X disorders. In one particularly notable example, a CGG repeat expansion in NOTCH2NLC leads to the creation of an AUG-initiated upstream open reading frame in the 5’ UTR that is generates a polyglycine-containing protein akin to FMRpolyG in FMR1 ( Liu et al, 2022 ; Boivin et al, 2021 ). This polyglycine protein is found within inclusions in patients with NIID and its generation is required to trigger inclusion formation and behavioral phenotypes in a mouse model of NOTCH2NLC associated NIID.…”
Section: Introductionmentioning
confidence: 99%